Environmental Dependence Of Different Colors Of Active Galactic Nucleus (Agn) Host Galaxies - Xin-Fa Deng; Zhi-Yong Wu (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Using the apparent-magnitude limited active galactic nucleus (AGN) host galaxy sample of the Sloan Digital Sky Survey Data Release 12 (SDSS DR12), we investigate the environmental dependence of the u-r, u-g, g-r, r-i and i-z colors of AGN host galaxies. Используя ограниченную по видимой величине выборку родительских галактик активных галактических ядер (АЯГ) из Sloan Digital Sky Survey Data Release 12 (SDSS DR12), исследована зависимость цветов u- r, u-g, g-r, r-i и i-z родительских галактик АЯГ от окружающей среды.
Keywords: Astrophysics